Clinical efficacy of sodium bicarbonate in treating pediatric metabolic acidosis with varying level of acid–base balance parameters: a real-world study - Huaqing Liu; Yanmei Cao; Xiaoyan Xue; Zhenjiang Bai; Shuiyan Wu (BMC Medicine, 2023)
Abstract Background Sodium bicarbonate (SB) infusion is commonly used to correct metabolic acidosis, but its clinical efficacy remains controversial. This study aims to investigate whether acid–base balance parameters should be a consideration for administering SB treatment. Methods Children with metabolic acidosis (pH < 7.35 and bicarbonate < 22 mmol/L) who were treated with or without 50 mg/ml SB injection were grouped and extracted from a retrospective cohort database of the Pediatric Intensive Care Unit. The interaction between acid–base balance parameters and SB treatment on mortality was analyzed through mortality curves and cross-effect models. Logistic regression was conducted to estimate the risk of death following SB treatment in the overall children as well as in subgroups, and potential confounding factors were adjusted for. After employing propensity score matching to account for confounding factors, further analysis was performed to evaluate the effectiveness of SB treatment within each chloride subgroup. Results A total of 5865 children with metabolic acidosis were enrolled, of which 2462 (42.0%) received SB treatment. In the overall population, it was found that SB treatment did not reduce hospital mortality or 28-day mortality. Interactions between acid–base balance parameters (chloride and anion gap) and SB treatment on mortality were observed. Subgroup analysis clarified that when chloride levels were below 107 mmol/L, children treated with SB had higher in-hospital mortality (29.8% vs 14.9%) and 28-day mortality (26.5% vs 13.4%), with adjusted ORs of 2.065 (95% CI, 1.435–2.97) and 1.947 (95% CI, 1.332–2.846), respectively. In contrast, when chloride levels were greater than or equal to 113 mmol/L, children treated with SB had a shorter stay in the PICU (median: 1.1 days vs 5.1 days, adjusted p = 0.004) and lower in-hospital mortality (4.3% vs 10.3%) and 28-day mortality (4.0% vs 8.4%), with adjusted ORs of 0.515 (95% CI, 0.337–0.788) and 0.614 (95% CI, 0.391–0.965), respectively. After controlling for confounding factors through matching, the impact of SB treatment on the risk of death in each chloride subgroup was consistent with the aforementioned results. However, treatment with SB did not significantly increase the risk of death in newborns or children with moderate to severe metabolic acidosis when chloride levels were below 107 mmol/L (p > 0.05). Conclusions The use of sodium bicarbonate for treating metabolic acidosis has been found to increase mortality in children with low chloride levels but decrease mortality in those with high chloride levels in this study. Further prospective multi-center clinical studies and basic research are needed to validate these findings.